AKTIVITAS PEMULIHAN EKONOMI MASYARAKAT TERDAMPAK PANDEMI COVID-19 DI KABUPATEN INHU - Ginda Ginda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Abstract The 2019 Corona Virus Disease (Covid-19) pandemic has spread throughout the region, including Inhu District, SimpangKelayang Village. The economic aspect is the impact that gets the most attention after the health aspect. The main problem that occurs in SimpangKelayang Village is that the economy of the business owner community is down (weak) due to the pandemic. Economic recovery must immediately be designed to overcome the economic crisis so that economic conditions do not sink into an economic depression. Through qualitative research methods, this study aims to reveal how the activities of the business community are trying to move from economic downturn during the COVID-19 pandemic. The economic recovery studied departs from Todaro & Smith's theory of the economic crisis. In SimpangKelayang Village the majority of the people are entrepreneurs, so the economic recovery strategy is to rely on the community business sector in developing trade, implementing digitalization in business and utilizing assistance in the form of Direct Cash Assistance (BLT), Micro, Small and Medium Enterprises (UMKM) and Economic Enterprises in the Save Village. Borrow (UEK-SP). Through the stretching of the business community, which is supported by assistance from the government as a driver of business development, finally the economy of the business community has experienced a significant increase as evidenced by the emergence of household savings and an increase in the amount of income.